Performance Evaluation of Underwater (UW) Welding System with Friction Stir Welding (FSW) Method on 316L Stainless Steel Exposed to Sea Water - Utomo, Edi; Prawirosastro, Carlos Lazaro (Maritime Park: Journal of Maritime Technology and Society, 2023)
Friction Stir Welding (FSW) is a solid-state welding technique that can produce high-quality joints without defects that commonly occur in liquid welding. However, FSW has limitations in underwater applications due to the friction between the tool and the material that causes a decrease in heat efficiency and shear force. To overcome this problem, this study proposes an underwater welding (UW) system with the FSW method on 316L stainless steel exposed to seawater. This UW-FSW system uses a high-speed rotating tool surrounded by an inert gas shroud to prevent direct contact between the tool and seawater. The aim of this study is to evaluate the performance of this UW-FSW system in terms of mechanical properties, microstructure, and corrosion resistance of 316L stainless steel joints. The results of this study show that the UW-FSW system can produce joints with better tensile strength, hardness, and corrosion resistance than conventional FSW. This is due to the rapid cooling, reduction of oxidation, and formation of a thicker passive layer on the joint surface. This study provides a contribution to the development of environmentally friendly and efficient underwater welding technology.